Initial Development of Bovine Placentation (Bos indicus) from the Point of View of the Allantois and Amnion - Assis Neto, A. C. [UNESP]; Santos, E. C. C. [UNESP]; Pereira, F. T. V. [UNESP]; Miglino, M. A. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
P>The aim of this study was to perform a morphological characterization of the initial bovine placental development, between 20 and 70 days post-insemination (p.i.), with emphasis on the differentiation of the allantois and amnion. After collection, the conceptuses were dissected, macroscopically measured and photographically documented. The extraembryonic membranes were cut into fragments measuring 5 cm2, and then fixed in 4% paraformaldehyde for analysis using light microscopy, and in 2.5% glutaraldehyde for use in scanning and transmission electron microscopy. The extraembryonic and fetal membranes presented variable degrees of development throughout the periods analysed. The macroscopic appearance of vascularization of the allantois, its attempt to merge with the chorium and the effective appearance of the first cotyledons in development were the events observed from 30 to 40 days of pregnancy. The measurements of the amnion increased gradually as gestation developed. The allantoic epithelia presented cellular dimorphism from 20 to 25 days of pregnancy, but was shown to be immature from 60 to 70 days of pregnancy.